Fintech Industry and Digital Financial Inclusion for Economic Development of an Inclusive Society in Indonesia - Patria Yunita; Mohammadtahir Cheumar (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2022)
This study aims to analyze cointegration relation between Fintech industry and digital financial inclusion in 34 provinces of Indonesia. Using the Binary Logistic Model, Panel Cointegration Test, and Panel Regression Model methods, this study concludes that there is a long-term relationship between fintech transactions and digital financial inclusion. it means economic development of an inclusice society in 34 provinces in Indonesia can be fufilled through fintech and digital inclusion. To analyze the relationship between variables we use Digital financial services, the number of accounts in digital financial services, conventional and sharia Rural Bank loan transactions as independent variables. Meanwhile, Fintech loan transactions as the dependent variable. To anticipate unobserved heterogeneity, dummy variables for pandemic conditions, inflation rate and economic growth were used as control variables.